Nutritional and therapeutic approaches to modulate NADPH oxidase-derived ROS signaling in platelets. - Violi, Francesco; Pastori, Daniele; Carnevale, Roberto; Pignatelli, Pasquale (Current Pharmaceutical Design, 2015)
Experimental and clinical studies provided evidence that formation of intra-platelet reactive oxidant species (ROS) is implicated in the process of thrombosis. Animal models demonstrated that enhanced ROS formation was associated with serious thrombotic complications and death. In recent years, nutritional and therapeutic approaches were tested to modulate ROS mediated thrombus formation. The use of a nutritional approach stems from the observation that foods rich in antioxidant elements, such as polyphenols, were able to modulate ROS formation. Similarly, some drugs used for different diseases (i.e. statins) showed the ability to modulate oxidative stress. Aim of this review is to summarize current evidences supporting the role of nutrients rich in polyphenols, such as olive oil and cocoa, and of some drugs, such as statins as antiplatelet agents interfering with the Nicotinamide Adenine Dinucleotide Phosphate (NADPH) Oxidase signaling. Indeed, for nutrients and statins, the antiplatelet activity seems to be dependent, at least in part, upon the inhibition of platelet NADPH oxidase–derived ROS formation, resulting in down-regulation of isoprostanes, which are pro-aggregating molecules, and up-regulation of nitric oxide, which is a platelet inhibitor.
Keywords: oxidative stress